Energy-Efficient Multi-Cell Massive MIMO Subject to Minimum User-Rate Constraints - Nguyen, Long Dinh; Tuan, Hoang Duong; Duong, Trung Q.; Poor, H. Vincent; Hanzo, Lajos (IEEE transactions on communications, 2021)
The capability of massive multiple-input multiple-output (mMIMO) systems supporting the throughput requirement of as many users as possible is investigated. The bottleneck of serving small numbers of users by a large number of transmit antennas in conventional mMIMO is unblocked by a new time-fraction-wise beamforming technique, which focuses signal transmission in fractions of a time slot. Based on this time-fraction-wise signal transmission, a new user service scheduling scheme for multi-cell mMIMO, whose cell-edge users suffer not only poor channel conditions but also multi-cell interference, is proposed to support a large user-population. We demonstrate that the numbers of users served by our multi-cell mMIMO within a time-slot may be as high as twice the number of its transmit antennas.